ARGUMENTS OF DIGNITY AND PLURALISM CONCERNS IN RECENT CONSTITUTIONAL COURT ADJUDICATION - Sperti , Angioletta (Revista Direitos Culturais, 2020)
The paper aims at discussing the growing importance of dignity discourse in human rights case law, in particular in recent constitutional and supreme courts cases on controversial rights. Starting from same-sex marriage rulings (as illustrative of a more general trend) the paper argues that dignity cannot be considered a mere “rhetorical tool” of courts, useful to tilt the balance in favour of one of the conflicting rights. On the contrary, dignity - with its wide and flexible meaning - marks the transition of new (or newly recognized) groups to social inclusion and provides a convenient language to mediate among conflicting claims of recognition without relying on more traditional equality arguments.